Characterization of Corrosion-resistant, Nanometer-thick, Layer-by-layer Aluminosilicate Coatings Prepared on Stainless Steel. (20th May 2016) - Habazaki, H.; Kimura, T.; Aoki, Y.; Tsuji, E.; Yano, T.; Shimizu, K.; Hassel, A.W.
Abstract: Highly corrosion-resistant, ∼65-nm-thick, layer-by-layer aluminosilicate coatings have been prepared by multiple spin casting on Type 430 stainless steel. These coatings have been characterized by field emission scanning electron microscopy, transmission electron microscopy, conductive atomic force microscopy, and micro-electrochemical measurements using a microcapillary cell. The coatings annealed at 400 °C are non-uniform and contain fine iron oxide nodules, which are formed in high densities on the 111 grain surface of the steel. The iron oxide nodules arise from the outward diffusion of the oxidized iron from the substrate through the coating. The coatings annealed at 400 °C are more insulating compared with those before annealing; however, the nodule sites are less insulating owing to the development of more conductive iron oxide channels in the coatings. A microcapillary cell study reveals that the coated specimens prepared from diluted precursor solutions by a layer-by-layer process exhibit higher pitting potential in 3.5 wt% NaCl solution compared with those prepared through a single-layer process. Moreover, the coated specimen obtained from the layer-by-layer process exhibits similarly high pitting potential even at the flaw sites in the coating; in contrast, the pitting potential in the flaw-containing regions of the coated specimen obtained from a single-layer process shifts towards the less noble direction. The layer-by-layer coating is also effective in suppressing the corrosion of the scratched region of the coated specimens, owing possibly to the excellent adhesion between the coating and the substrate.